Base Excision Repair of Oxidative DNA lesions in plants (Experimental biology, 2016)
Reactive oxygen species cause damage to all cellular macromolecules including membrane lipids, proteins and nucleic acids. Increased level of reactive oxygen species triggers cell death in plant and animal organisms indicating common mechanisms and targets of the free radicals action. DNA is the main cellular target for reactive oxygen species, currently, about 80 different types of oxidative damage to DNA have been identified including strand breaks, base and sugar modifications. In cells reactive oxygen species generate mostly non-bulky DNA lesions, the majority of which are substrates for the base excision repair.Until now, molecular characterizations of the DNA repair mechanisms have been mainly focused on E. coli, yeast and mammalian cells. As sessile organisms, plants are continuously exposed to a range of environmental genotoxic agents, including the ultraviolet (UV) component of sunlight, soil and air pollutants. In addition, plants continuously generate reactive oxygen species (ROS) as byproducts of metabolic reactions that take place in chloroplasts, mitochondria and peroxisomes. Oxidative damage to DNA caused by ROS is believed to be a major type of endogenous cellular damage. Moreover, plants lack a reserved germline and produce meiotic cells late in development, so mutations arising in somatic cells may be represented in gametes. To keep genome integrity and to assure faithful transfer of genetic information during cell division, living organisms develop several distinct DNA repair systems that remove and/or tolerate the DNA lesions. Although DNA repair mechanisms are well studied in bacteria, yeast, nematode and mammalian cells, little is known about the base excision repair pathway in plant. Recent advances in the study of DNA repair in higher plants show that they use mechanisms similar to those present in other eukaryotes to remove oxidized bases and other oxidative DNA lesions. In plants DNA repair is not only a fundamental cellular process for protecting cells against the damage, but is also essential to ensure faithful transmission of genetic information from one generation to the next.
Keywords: Reactive oxygen species; Base excision repair; DNA-glycosylase; AP-endonuclease; DNA-polymerase